Novel value-added phosphorus-potassium-activator fertilizers improve phosphorus use efficiency and crop yields. Issue 1 (1st January 2019) - Wang, Guiwei; Chen, Baocheng; Khan, Khuram Shehzad; Zheng, Wenkui; Liang, Hai; Han, Zhe; Chen, Jianqiu
ABSTRACT: It is thus essential and critical to enhance phosphorus (P) fertilizer use efficiency of crops to improve agricultural and environmental sustainability. A pot experiment was conducted to examine the impact of different kinds of value-added P-potassium (K)-activator fertilizers (VPAFs) on soil nutrient bioavailability, growth and yield of wheat-maize crops. Compared with that of the control (NPK) treatment, the wheat yields of VPAF treatments increased from 6.59% to 18.61%, and the maize yields increased from −0.22% to 15.58%. In addition, the P fertilizer utilization rate of VPAF treatments increased by an average of 10.87% and 5.75% for wheat and maize, respectively. Therefore, VPAF application in agriculture can introduce multiple benefits including increasing crop yield, improving fertilizer utilization efficiency, enhancing nutrient bioavailability, and reducing pollution.